Estimativa de NDVI no estado de Minas Gerais utilizando imagens dos satélites CBERS_2B/CCD e MSG/SEVIRI - Borges, Lidiane Aparecida (2010)
This study aimed to estimate and compare the vegetation index NDVI generated from images of satellites Meteosat-9 (high temporal resolution) with NDVI values generated from the CBERS 2B_CCD (high spatial resolution) in some regions of the state of Minas Gerais. Therefore, were generated maps of vegetation index (NDVI) for various times of the year using images from the Meteosat-9.Considered as the study area the state of Minas Gerais, located betweem the geographic coordinates 14° an 23° South and 39° e 51° of de longitude west of Greenwich. On tne satet of Minas Gerais some municipalities werw chosen to compare the values of NDVI, obtained by dthe satellite Meteosat with those obtaines by the CBER-2B.The study was conducted between the months of August, September and October 2009. The CBERS-2B images used were provived by inpe, and images from the engineering department of the Federal University of Lavras, where a laboratory receiving images directly from EUMETCast. The images were processed by the software ENVI. Maps have been prepared weekly NDVI for the months of August, September and October 2009, using data from Meteosat-9. On dates that correspond to the same time of year, were calculated in the regions under study the values of NDVI for the two satellites, to make the comparison between the values found. The maximum NDVI found by the Meteosat-9 were around 0.6 and minimum values around -0.2. The CBERS-2B has a medium spatial resolution, enabled him to perform a more detailed study of variation of NDVI of the municipalities. When comparing the NDVI values derived from images generated by the two satellites it was found that the satellite Meteosat-9, was not able to discriminate some areas in the images due to the heterogeneity of vegetation in the study area, because by having low resolution space it was not able to discriminate, some areas in the images generated.